STUDI ANALISIS MANAJEMEN PENGELOLAAN PRODI BIMBINGAN KONSELING ISLAM FITK UIN SUMATERA UTARA MEDAN - Tarmizi Situmorang (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2018)
This study aims to analyze the management of Islamic Guidance and Counseling study programs at the faculty of Tarbiyah and Teacher Training in UIN North Sumatra, Medan. The research method used is qualitative research methods, namely methods that are designed in such a way as to take and find data naturally. The subjects of this study were steakholders of the BKI FITK UIN North Sumatra study program. Data collection techniques are observation, interviews, and documentation. Data were analyzed by data presentation techniques, data reduction, and conclusion drawing. The results of the research can be summarized as follows: Islamic Guidance and Counseling Study Program at the Faculty of Tarbiyah and Teacher Training at UIN North Sumatra Medan conducts management management of study programs well, where the study program BKI FITK UIN North Sumatra optimizes the empowerment of existing resources to achieve the study program objectives vision, mission of study program. In addition, the vision, mission and objectives of the study program are also adjusted to the vision, mission, and objectives of the Faculty and University. Strategy Management is done is to arrange the distribution of subjects well, the curriculum is prepared in accordance with the needs of the community. Where of the 146 total credits there were 110 credits of courses related to the skills and skills of Guidance and Counseling, while as many as 36 credits were non BK courses and adjusted to the need to support BK's success. Then the subject is taught by lecturers who have the qualifications of Guidance and Counseling in Level 2 and Strata 3. In non-curricular activities, the study program of BKI FITK UIN North Sumatra Medan also forms the Al-Irsyad study forum which aims as a forum for students to do various discussion and creation that is useful for improving students' skills and knowledge about BK.Keywords: management, BKI study programPENDAHULUANPendidikan merupakan salah satu sasaran